Solvent-free polyurethane adhesive and application thereof
By using solvent-free polyurethane adhesives, using bio-based materials and specific polyester components, the durability of traditional solvent-based polyurethane adhesives in high temperature and high humidity environments is solved, and environmental protection, low cost and high performance are achieved. Preparation of adhesive.
Patent Information
- Application Number
- CN202411576196.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-06
AI Technical Summary
During the production and use of existing solvent-based polyurethane adhesives, they will bring organic gas emissions, endanger the environment and human health, and are prone to hydrolysis in high temperature and high humidity environments, resulting in a decrease in peeling force and affecting the durability of the composite film.
The polyurethane curing agent is prepared by bio-based materials, including PET-A and PET-B components and bio-based polyol ECR, and combined with diphenylmethane diisocyanate reaction to prepare polyurethane curing agent to form epoxy cinnamon Ristoroleic acid polyurethane adhesive.
This adhesive has the advantages of high temperature and humidity resistance, environmental protection and low cost. It improves the peeling strength and heat sealing strength of the composite film before and after boiling, meets the requirements of national standard GB/T 41168-2021, and reduces the petrochemical resources. dependence and environmental pollution.
Smart Images

Figure CN119432305A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyurethane adhesives, and in particular to a solvent-free polyurethane adhesive and application thereof. Background Art
[0002] Retort-resistant flexible packaging composite films are widely welcomed by the market because they can significantly extend the shelf life of food and retain the original flavor of food. Figure 1 As shown in the figure, the adhesives currently used for this type of film composite are mostly solvent-based polyurethane adhesives. However, during the production and use process, a large amount of organic gas emissions will be generated, which not only damages the environment but also endangers the health of construction workers. It is easy to hydrolyze in a high temperature and high humidity environment, resulting in a decrease in peeling force. In severe cases, it may even cause the composite film to delaminate or the cooking bag to rupture. At present, the water and heat resistance of polyurethane adhesives can be improved by modifying them. The modification methods include physical modification and chemical modification.
[0003] However, most of the raw material modifications of traditional polyurethane adhesives are overly dependent on petrochemical resources, which is not conducive to sustainable development.
[0004] For example, Chinese patent CN202111607212.2 discloses a flexible two-component polyurethane adhesive for flexible packaging composite film. The polyol component of the patent includes aliphatic-aromatic copolymerized polyester polyols modified by polyepoxides, ethyl acetate and additives. Although the polyurethane adhesive can improve bonding strength and tensile toughness, the components used in the polyurethane are not environmentally friendly materials. For example, ethyl acetate as an ester solvent is slightly toxic, and the emission process causes certain harm to the body, which is not conducive to sustainable development. In addition, there are also bio-based polyurethane adhesives, but the performance of current bio-based polyurethane adhesives is still far behind that of solvent-based polyurethane adhesives. Summary of the invention
[0005] The purpose of the present invention is to avoid the shortcomings of the prior art and provide a solvent-free polyurethane adhesive, which is made of bio-based materials and has the advantages of high temperature and humidity resistance, environmental protection and low cost.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A solvent-free polyurethane adhesive is provided, characterized in that it is prepared by the following steps, including:
[0008] Preparation of PET-A component:
[0009] 1,6-hexanediol, neopentyl glycol, ethylene glycol, and 1,2-propylene glycol are uniformly mixed, wherein the molar ratio of 1,6-hexanediol, neopentyl glycol, ethylene glycol, and 1,2-propylene glycol is 6:5:2:2 to 6:1:4:4; stirring and heating to 220 to 235° C., then adding tetrabutyl titanate, and keeping the temperature for reaction for 2 to 2.5 hours to obtain a mixture,
[0010] The acid value of the mixture is monitored. When the acid value is stable, the mixture is vacuumed and the acid value and hydroxyl value of the mixture are detected at set intervals. After the acid value and hydroxyl value to be detected reach the standard, the mixture is cooled to 120-150° C. and maintained under negative pressure for 2 hours to separate excess water in the mixture to obtain a PET-A component, whose chemical structure is as follows:
[0011]
[0012] Preparation of PET-B component:
[0013] 1,6-hexanediol, terephthalic acid, ethylene glycol and diethylene glycol are uniformly mixed, wherein the molar ratio of 1,6-hexanediol, terephthalic acid, ethylene glycol and diethylene glycol is 5:1:4:4 to 4:4:6:6; stirring and heating to 220 to 235° C., then adding tetrabutyl titanate, keeping the temperature for reaction for 2 to 2.5 hours, to obtain a mixture,
[0014] The acid value of the mixture is monitored. When the acid value is stable, the mixture is vacuumed and the acid value and hydroxyl value of the mixture are detected at set intervals. After the acid value and hydroxyl value to be detected reach the standard, the mixture is cooled to 120-150° C. and maintained under negative pressure for 2 hours to separate excess water in the mixture to obtain a PET-B component, whose chemical structure is as follows:
[0015]
[0016] Preparation of bio-based polyol ECR: Epoxidized soybean oil, cinnamic acid and ricinoleic acid are mixed evenly, wherein the molar ratio of epoxidized soybean oil, cinnamic acid and ricinoleic acid is 1:2:0.5, triethylamine is added as a catalyst, and the reaction is carried out at 120-150°C until the acid value of the reactant is stable, and the hydroxyl value of the product is tested and recorded to obtain bio-based polyol ECR, whose chemical structure is as follows:
[0017]
[0018] Preparation of polyurethane curing agent: PET-A and diphenylmethane diisocyanate are mixed evenly, and reacted at 65-80°C for 2.5-5h. When the isocyanate mass fraction ω NCO =15% to 18% and the reaction is stopped after stabilization to obtain a polyurethane curing agent, the chemical structure of which is as follows:
[0019]
[0020] Preparation of adhesive: The polyurethane curing agent is used as component A, and PTE-B and ECR are mixed as component B. The R value between component A and component B is 2.2-3. Component A and component B are mixed evenly to obtain epoxy cinnamon ricinoleic acid polyurethane adhesive, and its chemical structure is as follows:
[0021]
[0022] In some embodiments, when preparing the PET-A component, the amount of tetrabutyl titanate used is 0.004% to 0.006% of the total mass of the PET-A components.
[0023] In some embodiments, when preparing the bio-based polyol ECR, the amount of triethylamine used is 0.5% to 1.5% of the total mass of the bio-based polyol ECR.
[0024] In some embodiments, when preparing the adhesive, the weight ratio of the ECR to the PET-B is 5:0 to 0:5.
[0025] The beneficial effects of the solvent-free polyurethane adhesive of the present invention are as follows:
[0026] (1) The solvent-free polyurethane adhesive of the present invention is synthesized by designing the monomer molecular structure of two different polyesters PET-A and PET-B, wherein PET-A reacts with diphenylmethane diisocyanate to form a polyurethane curing agent Pre-PU-A with a curing function, and PET-B is mixed with a bio-based polyol ECR to form a polyurethane main agent with a bio-based group, wherein the bio-based polyol ECR is prepared from renewable biological resources epoxy soybean oil, ricinoleic acid, and cinnamic acid, and the benzene ring structure of cinnamic acid provides thermal stability for the adhesive. Qualitatively, the aliphatic long-chain structure of epoxy soybean oil and ricinoleic acid provides high hydroxyl value and hydrophobicity, which effectively improves the peel strength and heat sealing strength of the composite film adhesive before and after boiling. Therefore, the bio-based polyol ECR is mixed with polyester polyol PET-B and then reacted with Pre-PU-A as a curing agent to obtain epoxy cinnamon ricinoleic acid polyurethane adhesive. This adhesive maintains the high temperature and boiling resistance of solvent-based polyurethane adhesive and has environmentally friendly properties, overcoming the problems of traditional solvent-based polyurethane adhesives that pollute the environment and rely on petrochemical energy.
[0027] (2) The solvent-free polyurethane adhesive of the present invention introduces biomass raw materials into the B component of the prepared two-component polyurethane adhesive, which reduces the synthesis cost and alleviates the dependence of the polyurethane adhesive on petroleum-based raw materials and the pollution to the environment.
[0028] (3) The solvent-free polyurethane adhesive of the present invention, a bio-based two-component polyurethane adhesive prepared with epoxidized soybean oil, ricinoleic acid and cinnamic acid as raw materials, has high hydrophobicity and heat resistance, and successfully improves the peel strength before and after boiling and the heat sealing strength of the composite film. The peel force of the AI / RCPP layer is much higher than the requirements of the national standard GB / T 41168-2021.
[0029] The invention also provides an application of a solvent-free polyurethane adhesive, wherein the solvent-free polyurethane adhesive is mixed with a silane coupling agent, and the mixed material is used for a composite film. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic diagram of the structure of a flexible packaging composite film according to a specific implementation method.
[0031] Figure 2 It is a peeling diagram of the polyurethane adhesive before and after boiling in water according to a specific embodiment.
[0032] Figure 3 It is a diagram showing the inner layer peeling after the adhesive of a specific embodiment is cooked at 121°C.
[0033] Figure 4 is a DSC curve of a bio-based polyurethane adhesive according to a specific embodiment.
[0034] Figure 5 is the static water contact angle of the bio-based polyurethane adhesive according to a specific embodiment.
[0035] Figure 6 It is the infrared spectrum of each component of the polyurethane adhesive of a specific implementation method. DETAILED DESCRIPTION
[0036] The preferred embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although the preferred embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.
[0037] The terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The singular forms "a", "the" used in the present invention and the appended claims are intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0038] It should be understood that although the terms "first", "second", "third", etc. may be used to describe various information in the present invention, such information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of the present invention, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.
[0039] Example 1
[0040] This embodiment discloses a solvent-free polyurethane adhesive, which is prepared by the following steps, including:
[0041] Preparation of PET-A component:
[0042] 1,6-adipic acid (AA), neopentyl glycol (NPG), ethylene glycol (EG), and 1,2-propylene glycol (1,2-PG) are uniformly mixed, wherein the molar ratio of 1,6-adipic acid, neopentyl glycol, ethylene glycol, and 1,2-propylene glycol is 6:5:2:2 to 6:1:4:4; stirred and heated to 220 to 235° C., then tetrabutyl titanate is added, and the mixture is kept warm for reaction for 2 to 2.5 hours to obtain a mixture.
[0043] The above-mentioned 1,6-hexanediol, neopentyl glycol, ethylene glycol and 1,2-propylene glycol are mixed for the esterification reaction of acid and alcohol. In the early stage of the reaction, the reaction can proceed smoothly without adding a catalyst. When entering the late stage of the reaction, the acidity in the system decreases, and the self-catalytic efficiency is too low. It takes dozens of hours to make the acid value of the product meet the standard, which seriously affects the production efficiency. At this time, the reaction is accelerated by adding a catalyst tetrabutyl titanate.
[0044] If the acid value of the product is too high, it will cause excessive side reactions with the curing agent during the subsequent preparation of the glue. The acid value of the mixture is monitored. When the acid value is stable, it means that the esterification stage reaction is close to stopping. The mixture is then vacuumed to remove the small molecule diol from the polymerization system through the ester exchange reaction, and finally a high molecular weight polymer is obtained. At this time, the vacuum is gradually increased to avoid flooding. The acid value and hydroxyl value of the mixture are detected at set intervals. After the acid value and hydroxyl value to be detected reach the standard, the temperature is lowered to 120-150°C and maintained under negative pressure for 2 hours to separate excess water in the mixture to obtain the PET-A component. The reaction process and chemical structure are as follows:
[0045]
[0046] In the esterification stage, the diacid and diol undergo esterification reaction to form ester bonds through catalysis, obtaining low molecular weight esterification products. In the subsequent polycondensation stage, high temperature and vacuum conditions are used to remove the small molecular diol from the polymerization system through ester exchange reaction, and finally obtain high molecular weight polymers.
[0047] Preparation of PET-B component:
[0048] 1,6-adipic acid (AA), terephthalic acid (PTA), ethylene glycol (EG), and diethylene glycol (DEG) are uniformly mixed, wherein the molar ratio of 1,6-adipic acid, terephthalic acid, ethylene glycol, and diethylene glycol is 5:1:4:4 to 4:4:6:6; stirred and heated to 220 to 235° C., then tetrabutyl titanate is added, and the mixture is kept warm for reaction for 2 to 2.5 hours to obtain a mixture.
[0049] The acid value of the mixture is monitored. When the acid value is stable, the mixture is vacuumed and the acid value and hydroxyl value of the mixture are detected at set intervals. After the acid value and hydroxyl value to be detected reach the standard, the mixture is cooled to 120-150° C. and maintained under negative pressure for 2 hours to separate excess water in the mixture to obtain a PET-B component, whose chemical structure is as follows:
[0050]
[0051] The polyester polyol PET-B component differs from the polyester polyol PET-A only in raw materials and content. By adjusting the content of the raw material components, polyester polyol PET components with different molecular weights can be obtained.
[0052] Preparation of bio-based polyol ECR: Epoxidized soybean oil, cinnamic acid and ricinoleic acid are mixed evenly, wherein the molar ratio of epoxidized soybean oil, cinnamic acid and ricinoleic acid is 1:2:0.5, triethylamine is added as a catalyst, and the reaction is carried out at 120-150°C until the acid value of the reactant is stable, and the hydroxyl value of the product is tested and recorded to obtain bio-based polyol ECR. The reaction process and chemical structure are as follows:
[0053]
[0054] Preparation of polyurethane curing agent: PET-A and diphenylmethane diisocyanate are mixed evenly, and reacted at 65-80°C for 2.5-5h. When the isocyanate mass fraction ω NCO =15% to 18% and the reaction is stopped after stabilization to obtain a polyurethane curing agent. The reaction process and chemical structure are as follows:
[0055]
[0056] The theoretical addition amount of diphenylmethane diisocyanate is calculated by designing the mass fraction of isocyanate in advance. When no side reaction occurs, the quantitative relationship of the above variables satisfies the following relationship:
[0057]
[0058] Where m is the theoretical amount of diphenylmethane diisocyanate required per 100g of polyester polyol (g), ω NCO To design the theoretical mass fraction (%) of isocyanate groups to be synthesized, OH v is the hydroxyl value of the polyester polyol (mgKOH / g).
[0059] Preparation of adhesive: The polyurethane curing agent is used as component A, and PTE-B and ECR are mixed as component B. The R value between component A and component B is 2.2-3. Component A and component B are mixed evenly to obtain epoxy cinnamon ricinoleic acid polyurethane adhesive. The reaction process and chemical structure are as follows:
[0060]
[0061] Because there is a relationship between the isocyanate index R value as follows:
[0062] Where: m p 、m B are the masses (g) of component A and component B respectively; R is the molar ratio of isocyanate group to hydroxyl group of the two components; ω NCO is the mass fraction of isocyanate groups in component A (%); OH is the hydroxyl value of component B (mgKOH / g).
[0063] Polyurethane adhesives with different structural properties were prepared by adjusting the distribution ratio of the two groups of adhesives to reduce the impact of subsequent adhesive distribution.
[0064] In this embodiment, when preparing the PET-A component, the amount of tetrabutyl titanate used is 0.004% to 0.006% of the total mass of the PET-A components, and the amount can be adjusted according to actual needs.
[0065] In this embodiment, when preparing the bio-based polyol ECR, the amount of triethylamine used is 0.5% to 1.5% of the total mass of the bio-based polyol ECR, and the amount can be adjusted according to actual needs.
[0066] In this embodiment, when preparing the adhesive, the weight ratio of the ECR to the PET-B is 5:0 to 0:5, and the amount can be adjusted according to actual needs.
[0067] In this embodiment, the solvent-free polyurethane adhesive is mixed with 0.5% to 1% of the total mass of a silane coupling agent, and the mixture is used for a composite film.
[0068] Effect verification
[0069] To further illustrate the effect of the solvent-free polyurethane adhesive obtained by the present invention, the following test was conducted.
[0070] Test Example 1
[0071] Preparation of polyester polyol PET-A: The corresponding raw materials AA, NPG, EG, and 1,2-PG are added to a four-necked flask at a molar ratio of 6:3:3:3, a reaction device is built, stirring is started, and the temperature is heated from room temperature to 230°C, and the temperature of the top thermometer is kept at 100±2°C during the period. When the temperature reaches 230°C, 0.004% tetrabutyl titanate is added to the four-necked flask and kept warm for 2h. Test the acid value, and when the acid value no longer changes, start to vacuum at a rate of -0.01MPa / 30min, and test the changes in the acid value and hydroxyl value of the reaction product at intervals. After the test results are qualified, cool down to 130°C, keep at -0.1MPa for 2h to remove excess moisture in the polyester as much as possible, and finally stop the reaction, and discharge the material after cooling down. Polyester PET-B and polyester PET-A are synthesized using the same preparation process, and the molar ratio of raw materials is AA:PTA:EG:DEG=5:2:5:5.
[0072] Synthesis of bio-based polyol ECR: ESO, CA, and RA were added in a feed ratio of 1:2:0.5 in a 500 mL four-necked flask equipped with a stirring rod, a thermometer, and a reflux condenser. 1% of TEA was added as a catalyst. The reaction was carried out at 140 °C until the acid value of the reactants no longer changed. The reaction was stopped and the hydroxyl value of the product was tested and recorded.
[0073] Synthesis of polyurethane curing agent: Preparation of 17% ω NCO After calculation, add 100g of polyester polyol PET-A and 153g of MDI which have been dehydrated into a four-necked flask, keep the reaction temperature at 75°C, and react for 2h. Take samples at regular intervals to test the isocyanate mass fraction of the reactants. Stop the reaction when the isocyanate mass fraction of the reaction product reaches the theoretical value and tends to be stable, and seal and store for later use. The polyurethane curing agent sample is recorded as Pre-PU-A.
[0074] PTE-B and ECR were mixed in mass ratios of 5:0, 4:1, 3:2, 2:3, 1:4, and 0:5 as component B, Pre-PU-A was used as component A, and components A and B were mixed with an R value of 2.5 to prepare epoxy cinnamon castor oil-based polyurethane adhesive PU-ECR, and then 0.5% of the total mass of the adhesive was added with a silane coupling agent for film composite.
[0075] like Figure 1 The schematic diagram of the flexible packaging composite film structure shown in the figure refers to the test method in GB / T 41168-2021 "Plastic and aluminum foil composite film and bag for food packaging" to carry out peeling force, heat sealing strength and cooking resistance tests on the composite film. The testing instrument is the XLW tensile testing machine of Jinan Languang Electromechanical Technology Co., Ltd.
[0076] Figure 2 The peeling force diagram of the inner and outer layers before and after boiling shows that, as the mass fraction of ECR increases, the peeling force before boiling increases first and then decreases. When the ECR content is 60%, the AI / RCPP layer reaches a maximum value of 7.03N. This is because the ECR molecule has multiple functional groups and a high functionality, which can increase the crosslinking degree between the adhesive molecules. However, when the ECR content exceeds a certain amount, a larger molecular group is formed, resulting in the -OH group being wrapped in the molecular group, which is difficult to react completely, resulting in a decrease in peeling force. The trend of heat seal strength change is consistent with the peeling force of the AI / RCPP layer, reaching a maximum value of 53.4N / 15cm when the ECR content is 80%. After boiling, as the mass fraction of ECR increases, the degree of decrease in the peeling force of the AI / RCPP layer decreases. This is because the benzene ring structure of cinnamic acid enhances its heat resistance, and the long chain structure of ricinoleic acid enhances its hydrolysis resistance. The synergistic effect of the two improves the hydrothermal resistance of the adhesive. When the addition amount is 80%, the peeling force reaches a maximum value of 5.59N. The peeling force of the layer with 100% ECR increased to 4.95N after boiling. This is because as the temperature rises, the ECR molecular groups effectively unfold and react with the substrate surface, and expose the encapsulated hydroxyl groups to react with the unreacted -NCO groups, which enhances the hydrogen bonding with the substrate and increases the peeling force. When the boiling conditions are increased to 121℃ and boiled for 30min, the peeling force of the AI / RCPP layer is as follows: Figure 3 As shown in the figure, even the polyurethane adhesive PU-ECR-0 with terephthalic acid added has a peel force of only 2.1 N. However, as the ECR content increases, its peel force gradually increases, reaching a maximum value of 6.2 N when the mass fraction is 100%. This is because when the temperature rises further, the ECR molecular groups unfold more completely, exposing more -OH groups, and reacting more thoroughly with -NCO, further enhancing the surface interaction with the substrate and increasing the peel force.
[0077] Preparation of flexible packaging composite film
[0078] The preparation of flexible packaging bags is divided into two processes: film lamination and heat-sealing bag making. Aluminum foil (AI), polyethylene terephthalate film (PET) and retort-resistant polypropylene cast film (RCPP) are cut into rectangles of 30cm×19cm. PET is fixed on the glue coating sample table as the outer layer, and the mixed polyurethane adhesive is evenly coated on the PET surface with an amount of 1.2-1.5g / m2, and the aluminum foil is pressed with the PET. Repeat the above steps to compound the RCPP film with the aluminum foil to obtain a composite film of PET / AI / RCPP structure. The composite film is placed in an oven at 40℃ for 72h. After the adhesive is completely cured, it is cut into 15cm wide strips for peeling force testing. The cured composite film is hot-pressed using a heat seal tester to prepare a retort bag. The retort bag is filled with tap water exceeding 1 / 2 of its volume and the air is exhausted. The upper and lower temperatures of the heat seal tester are set to 160℃.
[0079] Test Example 2
[0080] The steps are the same as those in Experiment 1, except that the raw material ratio of polyester PET-A is AA:NPG:EG:1,2-PG at a molar ratio of 6:2:3.5:3.5. The raw material ratio of polyester PET-B is AA:PTA:EG:DEG=5:3:6:6. The reaction temperature of bio-based polyol ECR synthesis is 150°C. NCO =16%, MDI added amount is 138g, and silane coupling agent added amount is 1% of the total mass.
[0081] Figure 4 The DSC curves of bio-based polyurethane adhesives with different ECR mass fractions are shown in the figure. The polyurethane glass transition temperature (Tg) has been marked in the table in the figure. The glass transition temperature is related to the composition structure of polyester polyols and is greatly affected by the rigidity of the soft segment. As the ECR mass fraction increases, the rigidity of the polyurethane adhesive increases and the glass transition temperature increases. This is because the cinnamic acid content in ECR is high and the rigid benzene ring structure accounts for a large proportion. Compared with the adhesive without ECR, the glass transition temperature is significantly increased.
[0082] Test Example 3
[0083] The steps are the same as those in Example 2. However, the raw material ratio of polyester PET-B is AA:PTA:EG:DEG=4:4:6:6, and the polyester polyol synthesized without adding terephthalic acid is the control group, and its raw material ratio is AA:PTA:EG:DEG=8:0:6:6. The reaction temperature of bio-based polyol ECR is 135°C, and the amount of triethylamine added is 1.5% of the total mass. NCO =18%, MDI addition amount is 168g. Silane coupling agent addition amount is 0.5% of the total mass.
[0084] Figure 5 The surface water contact angle diagram of different polyurethane adhesives is used to characterize the hydrophobicity of polyurethane adhesives by static water contact angle. As shown in the figure, polyurethane adhesives all have high hydrophobicity. The contact angle of adhesives without added benzene ring structure is 89.3°, and the contact angle of polyurethane adhesives with added terephthalic acid is 82.7°. This may be because as the content of terephthalic acid increases, the corresponding content of adipic acid with a long-chain fatty structure decreases, and the hydrophobicity decreases. And the contact angle of adhesives with added ECR is greater than that of PU-ECR-0 adhesive. After the addition amount exceeds 20%, the contact angle tends to be stable. This is because the addition of ECR increases the cross-linking degree of the adhesive, and the increase in aliphatic long chains enhances the hydrophobicity of the adhesive. However, with the increase of ECR mass fraction, the hydrophilic groups introduced by the unreacted cinnamic acid and ricinoleic acid also increase accordingly, which reduces its hydrophobicity. The two effects influence each other, so that the contact angle tends to the range of 89.8°~91.6°. It can be concluded that the polyurethane adhesives prepared by bio-based polyol ECR have high hydrophobicity.
[0085] Comparative Example 1
[0086] The other conditions were the same as those in Experimental Example 1, but the polyester polyol synthesized without adding terephthalic acid was used as the control group, and the raw material ratio of AA:PTA:EG:DEG was 8:0:6:6.
[0087] Figure 6 The infrared spectra of each component of polyurethane adhesive are shown in the figure. 3500cm -1 The broad peak at 2950cm is the stretching vibration peak of hydroxyl-OH, indicating that polyester polyol contains abundant hydroxyl groups. -1 and 2870cm -1 The characteristic absorption peaks of CH2 and CH3 stretching vibrations can be seen in the spectrum of the curing agent Pre-PU-A. The characteristic peak of -OH disappears at 3350cm -1 and 1530cm -1 The stretching vibration peak and bending vibration peak of -NH in the carbamate group appear at 1610cm-1, the characteristic peak of C=O in the carbamate group appears at 2260cm-1, and the characteristic peak of C=O in the carbamate group appears at 1610cm-1. -1 The new peak at 1740cm-1 is attributed to the C=N stretching vibration peak of -NCO. 729cm-1 is the C=O stretching vibration peak of the ester group. -1 The peak at 1690cm is the out-of-plane bending vibration peak of =CH on the benzene ring. -1 The carbonyl C=O characteristic peak of cinnamic acid and ricinoleic acid is at 1640 cm -1 The characteristic peak of epoxy group of epoxidized soybean oil appears at 829cm -1At, and the product is 829cm -1 The peak at 3500cm -1 The characteristic peak of -OH appears at , which is because the epoxy group on the epoxidized soybean oil undergoes a ring-opening reaction with the carboxyl group on cinnamic acid and ricinoleic acid, consuming the epoxy group and generating hydroxyl group.
[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A solvent-free polyurethane adhesive, characterized in that: Prepared by the following steps, including: Preparation of PET-A component: 1,6-hexanediol, neopentyl glycol, ethylene glycol, and 1,2-propylene glycol are uniformly mixed, wherein the molar ratio of 1,6-hexanediol, neopentyl glycol, ethylene glycol, and 1,2-propylene glycol is 6:5:2:2 to 6:1:4:4; stirring and heating to 220 to 235° C., then adding tetrabutyl titanate, and keeping the temperature for reaction for 2 to 2.5 hours to obtain a mixture, The acid value of the mixture is monitored. When the acid value is stable, the mixture is vacuumed and the acid value and hydroxyl value of the mixture are detected at set intervals. After the acid value and hydroxyl value to be detected reach the standard, the mixture is cooled to 120-150° C. and maintained under negative pressure for 2 hours to separate excess water in the mixture to obtain a PET-A component, whose chemical structure is as follows: Preparation of PET-B component: 1,6-hexanediol, terephthalic acid, ethylene glycol and diethylene glycol are uniformly mixed, wherein the molar ratio of 1,6-hexanediol, terephthalic acid, ethylene glycol and diethylene glycol is 5:1:4:4 to 4:4:6:6; stirring and heating to 220 to 235° C., then adding tetrabutyl titanate, keeping the temperature for reaction for 2 to 2.5 hours, to obtain a mixture, The acid value of the mixture is monitored. When the acid value is stable, the mixture is vacuumed and the acid value and hydroxyl value of the mixture are detected at set intervals. After the acid value and hydroxyl value to be detected reach the standard, the mixture is cooled to 120-150° C. and maintained under negative pressure for 2 hours to separate excess water in the mixture to obtain a PET-B component, whose chemical structure is as follows: Preparation of bio-based polyol ECR: Epoxidized soybean oil, cinnamic acid and ricinoleic acid are mixed evenly, wherein the molar ratio of epoxidized soybean oil, cinnamic acid and ricinoleic acid is 1:2:0.5, triethylamine is added as a catalyst, and the reaction is carried out at 120-150°C until the acid value of the reactant is stable, and the hydroxyl value of the product is tested and recorded to obtain bio-based polyol ECR, whose chemical structure is as follows: Preparation of polyurethane curing agent: PET-A and diphenylmethane diisocyanate are mixed evenly, and reacted at 65-80°C for 2.5-5h. When the isocyanate mass fraction ω NCO =15% to 18% and the reaction is stopped after stabilization to obtain a polyurethane curing agent, the chemical structure of which is as follows: Preparation of adhesive: The polyurethane curing agent is used as component A, and PTE-B and ECR are mixed as component B. The R value of -NCO / OH between component A and component B is 2.2-3. Component A and component B are mixed evenly to obtain epoxy cinnamon ricinoleic acid polyurethane adhesive, and its chemical structure is as follows:
2. The solvent-free polyurethane adhesive according to claim 1, characterized in that: When preparing the PET-A component, the amount of tetrabutyl titanate is 0.004% to 0.006% of the total mass of the components of PET-A; When preparing the PET-B component, the amount of tetrabutyl titanate used is 0.004% to 0.006% of the total mass of the various components of PET-B.
3. The solvent-free polyurethane adhesive according to claim 1, characterized in that: When preparing the bio-based polyol ECR, the amount of triethylamine used is 0.5% to 1.5% of the total mass of the bio-based polyol ECR.
4. The solvent-free polyurethane adhesive according to claim 1, characterized in that: When preparing the adhesive, the weight ratio of the ECR to the PET-B is 5:0 to 0:
5.
5. The use of the solvent-free polyurethane adhesive according to any one of claims 1 to 4, characterized in that: The solvent-free polyurethane adhesive is mixed with 0.5% to 1% of the total mass of a silane coupling agent, and the mixed material is used for a composite film.
Citation Information
Patent Citations
Polyol component of flexible two-component polyurethane adhesive for flexible packaging composite film, preparation method and application thereof
CN114437326B
Low free MDI monomer bicomponent solvent-free
CN101880516A
Polyol component of flexible bi-component polyurethane adhesive for flexible package composite film as well as preparation method and application of polyol component
CN114437326A
Polyurethane adhesive for flexible package and preparation method thereof
CN117285900A
Solventless adhesive composition
TW202204465A
